Respostas
respondido por:
3
a12= a5-(12-5)r
60=25-7r
7r=35
r=5
60=25-7r
7r=35
r=5
respondido por:
3
a5 = 25
a12 = 60
an = a1 + (n - 1).r
a5 = a1 + 4.r
25 = a1 + 4.r ⇒ a1 = 25 - 4.r (1)
a12 = a1 + 11.r
60 = a1 + 11.r ⇒ a1 = 60 - 11.r (2)
Igualando (1) e (2), temos:
25 - 4.r = 60 - 11.r
11.r - 4.r = 60 - 25
7.r = 35
r = 35/7
r = 5
Resposta: r = 5
Espero ter ajudado.
a12 = 60
an = a1 + (n - 1).r
a5 = a1 + 4.r
25 = a1 + 4.r ⇒ a1 = 25 - 4.r (1)
a12 = a1 + 11.r
60 = a1 + 11.r ⇒ a1 = 60 - 11.r (2)
Igualando (1) e (2), temos:
25 - 4.r = 60 - 11.r
11.r - 4.r = 60 - 25
7.r = 35
r = 35/7
r = 5
Resposta: r = 5
Espero ter ajudado.
ProfRafael:
Obrigado!
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás